Penegakan Hukum Nasional dan Hukum Internasional Terhadap Kejahatan Cyber Espionage Pada Era Society 5.0 - Hamdan Mustameer (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2022)
The era of Society 5.0 is a condition of society that is required to solve various challenges and social problems by utilizing various innovations that were born in the era of the Industrial Revolution 4.0 such as the Internet on Things, Big Data, Artificial Intelligence, and robots to improve the quality of human life. The new things in Era Society 5.0 should not change law enforcement based on decision-making, the freedom of legal institutions in deciding cases, the professionalism of the apparatus, and public transparency. The rapidity of this era in entering the country during the Covid-19 pandemic, triggering cybercrimes that use new tools such as virus spread, and cracking. One of the crimes that the state is vulnerable to is Cyber Espionage. This crime is an act of espionage that takes advantage of advances in technology and information. As a state of law, Indonesia is required to have policies that regulate Cyber Espionage actions while still paying attention to aspects of international law so that law enforcement in Indonesia can run smoothly. To find out the readiness of Indonesian law in facing the threat of Cyber Espionage, we write this article with a normative juridical research with three approaches, conceptual approach, statutory approach, and comparative approach. The results of our research show that the national legal instruments in Indonesia are still limited to the Electronic Information and Transaction Law (ITE), Government Regulations regarding its implementation, Presidential Regulations on National Defense (Perpreshanneg), and the absence of policies that specifically regulate cyber crimes.